(3GbJWGa RgQGJ GdCafGf ef OhMI bGajI GHf GdhfGfs - (3CHh MGeO Gdecj Hf eMeO Hf Ydj GdHWGhQj GdTQja GdMSjfj,J (B1354 (3g` s; (3CMeO Hf eMeO Hf eMeO GdJhGJj GdMejQj, CHh GdYHGS GdeYQha HGHf GdnhqfGf,J (B1187 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3adeG ef Gddg SHMGfg Ydqj, hCJe fYeJg dOj acGf eeG hdYJ Hg bOjekG, hCJNPJg SejQkG hCfjSkG hfOjekG (B"(3GdbUjOI GdbGajI GdeYQhaI HGdTebebjI(B" (3MJi OGfjJ ef eYGfjgG GdZQV s
(3BNQgG (B:s
(3bGd eDda Gdecj Hf eMeO ZaQ Gddg PfhHg, hSQ Hefg YjhHg(B: (3gPG BNQ eG QefG JMQjQg hCbUi eG CQOfG JSWjQg hcGf JeGe JbjjOg HYO GdYTGA GdCNjQI ef jhe GdSHJ YTQj TgQ QeVGf GdeYXe s
(3GdeNWhW Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B243 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B155s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B51 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(123 (3O(B) s
Keywords: (3GdCOHs